Transmit Beamforming Techniques for Multicast Wireless Communication Systems - Özbek, Berna; Özbek, Berna; Le Ruyet, Didier (Institute of Electrical and Electronics Engineers Inc., 2009)
In this paperg transmit beamforming algorithm is designed for multicast wireless communication providing only one beam and multiple beams. The reduced complexity algorithms are imyproved the system performance with multiple transmit beamy forming techniques.
IEEE 17th Signal Processing and Communications Applications Conference